Utility of Heidelberg retinal tomography as a screening tool for analyzing retinal nerve fiber layer defects - Belyea DA (Dove Medical Press, 2014)
David A Belyea, Rashed N Alhabshan, Sankaranarayana P Mahesh, Gregory S Gertner, Mirsad M Ibisevic,† Abdullah S Habib, Jacob A Dan Department of Ophthalmology, The George Washington University, Washington, DC, USA †Dr Mirsad Ibisevic passed away on January 4, 2013 Context: Although Heidelberg retinal tomography (HRT)-generated topographic images have been studied extensively for the detection of retinal nerve fiber layer (RNFL) defects, little is known about the role of HRT-generated surface reflectivity images in the detection of RNFL defects in either patients with glaucoma or glaucoma suspects. Aims: To evaluate the effectiveness of HRT version II (HRT II) optic nerve reflectivity images in uncovering RNFL defects in an outpatient population evaluated for glaucoma.Study design/materials and methods: In 102 consecutive eyes from 60 patients evaluated for glaucoma in an academic-based practice, HRT II optic nerve images were prospectively imaged and compared with clinical optic nerve exam techniques to see if HRT II was able to detect RNFL defects overlooked in clinical practice. Results: Nine eyes (8.8%) were found to have RNFL defects recognized by screening with HRT II. Of these nine eyes, eight (88.9%) were recognized to demonstrate RNFL defects by conventional examination techniques. One additional eye had an RNFL defect seen on physical exam that was not detected by HRT. Conclusion: In academic practice, HRT II may be helpful in complementing conventional exam techniques in the recognition and documentation of acquired RNFL loss. Keywords: HRT, RNFL defect, optic nerve, glaucoma, glaucoma suspect